John Hick: A Critical Introduction and Reflection - Athappilly, Sebastian (Journal of Dharma, 2003)
David Cheetham, John Hick: A Critical Introduction and Reflection, Hampshire: Ashgate, 2003, pages viii + 189, ISBN: 0-7546-1599-5.